A blockchain-based trusted security zone architecture. Issue 5 (17th September 2019) - Jo, Jeong Hoon; Rathore, Shailendra; Loia, Vincenzo; Park, Jong Hyuk
Abstract : Purpose: The purpose of this paper is to propose a trusted security zone architecture that uses a blockchain technology to provide secure sharing of data in the security zone while maintaining the integrity, confidentiality and availability of data. The blockchain uses a distributed network to ensure data availability and uses public ledgers to ensure the integrity and confidentiality of data. Design/methodology/approach: The proposed architecture uses a blockchain technology to provide secure sharing of data in the security zone while maintaining the integrity, confidentiality and availability of data. The blockchain uses a distributed network to ensure data availability and uses public ledgers to ensure the integrity and confidentiality of data. Findings: Analysis of the proposed architecture with a use case scenario demonstrates that it provides a robust security measure against unauthorized network intrusions. Originality/value: Unlike the existing security zone, this paper adopts a method of storing data by using blockchain. It meets the need to study integrated authentication management methods of future research.